Implementasi Kebijakan Program Pemberdayaan Masyarakat Sejahtera, Mandiri dan Bermartabat (P2MSMART) Di Kota Salatiga (Studi Di Kelurahan Tegalrejo dan Kelurahan Ledok) - Kiki Diana Pratiwi; Fitriyah .; achmad Taufiq (Journal of Politic and Government Studies, 2015)
Development program is a program created by the government aims to fillthe needs of the community. P2M-Smart program is a development program conducted in Salatiga since 2012. Village Tegalrejo and Ledok are two of the 22 villages in Salatiga who receive grants P2M-Smart for physical development activities. Overall this program was successful. However, the implementation of this program find some obstacles.The purpose of this study to describe the implementation of P2M-Smart program in 2012, and identifies the factors that become the driving and inhibiting the implementation of the program. The method used in this research is descriptive qualitative method and data collection techniques is by interviews and documentation.Based on the results it was concluded that the implementation of P2MSmart in the Village Tegalrejo and the Village Ledok are able to achieve the goals and objectives of the program and in accordance with the expectations of society. Beside that, people also are excited to support this program. However, the implementation of this program encountered several obstacles, like the weather and lack of builders.The recommendation that can be delivered include the City Government is expected to maintain and develop P2M-Smart program and other activities that can support the local economy and education, as well as possible while maintaining the cooperation and coordination between the parties involved. So that, the implementation of P2M-Smart in the next years can run well and as expected by the government and society.